Effect of photon fluence rates of white and blue-green light on growth efficiency and Pigment Content Of Three Diatom Species In Batch Cultures - MP Sánchez-Saavedra; D Voltolina (Ciencias Marinas, 2002)
This study provides information on the combined effect of light quality and photon fluence rates (light intensity) on growth efficiency and pigment content of the coastal plankton diatoms Chaetoceros sp., Skeletonema costatum and Thalassiosira pseudonana. The relative growth efficiencies of the three species were significantly higher at 210 µE m-2s-1, under mixed bluegreen light for Chaetoceros sp. and S. costatum, and with white light for T. pseudonana. The chlorophyll a contents of the three species grown under blue-green light, alone or mixed with white light, were significantly higher (P < 0.001) than those with white light and, in all cases, contents were lower at high photon fluence rates, while carotenoids showed inverse trends. The relative growth efficiencies of the three species were significantly different (P < 0.001). There were also changes in the relative pigment concentrations associated with the growth phase, probably due to autoshading.